Language Acquisition: Classroom Language Acquisition for Kindergarten Students - Anggita Pratiwi; Alemina Br. Perangin-angin (Departement of Mathematics Education, 2023)
This paper explained about the language acquisition of the kindergarten students. The language acquisition involved the mini research by using qualitative approach. The researcher did observation to TK At Thahirah Islamic Marelan and did case study to know the acquisition of classroom language in that school. The researcher also identified the process of children’ language acquisition and also identified the process of acquisition. In this paper also explain the relation of data in the field with expert opinion about language acquisition